Racial and Ethnic Disparities in Pain Management of Children With Limb Fractures or Suspected Appendicitis: A Retrospective Cross-Sectional Study - Guedj, Romain; Marini, Maddalena; Kossowsky, Joe; Berde, Charles B.; Kimia, Amir A.; Fleegler, Eric W. (Frontiers in Pediatrics, 2021)
Objective: To evaluate whether racial/ethnical differences in analgesia administration existed in two different cohorts of children with painful conditions: children with either limb fracture or suspected appendicitis. Methods: Retrospective cross-sectional analysis of children visiting a pediatric emergency department (Boston Children Hospital) for limb fracture or suspected appendicitis from 2011 to 2015. We computed the proportion of children that received any analgesic treatment and any opioid analgesia. We performed multivariable logistic regressions to investigate race/ethnicity differences in analgesic and opioid administration, after adjusting for pain score, demographics and visit covariates. Results: Among the 8,347 children with a limb fracture and the 4,780 with suspected appendicitis, 65.0% and 60.9% received any analgesic treatment, and 35.9% and 33.4% an opioid analgesia respectively. Compared to White non-Hispanic Children, Black non-Hispanic children and Hispanic children were less likely to receive opioid analgesia in both the limb fracture cohort (Black: aOR= 0.61 [95%CI, 0.50-0.75]; Hispanic aOR= 0.66 [95%CI, 0.55-0.80]) and in the suspected appendicitis cohort (Black: aOR= 0.75 [95%CI, 0.58-0.96]; Hispanic aOR= 0.78 [95%CI, 0.63-0.96]). In the limb fracture cohort, Black non-Hispanic children and Hispanic children were more likely to receive any analgesic treatment (non-opioid or opioid) than White non-Hispanic children (Black: aOR= 1.63 [95%CI, 1.33-2.01]; Hispanic aOR= 1.43 [95%CI, 1.19-1.72]) Conclusion: Racial and ethnic disparities exist in the pain management of two different painful conditions, which suggests true inequities in health care delivery. To provide equitable analgesic care, emergency departments should monitor variation in analgesic management and develop appropriate universal interventions.